(untitled) (Archaeologia Adriatica, 2022)
Archaeological excavation of a late antique tower at the position Gradac in the village of Ošlje resulted in uncovering small finds that are analyzed in this paper. Most artifacts can be dated to Late Antiquity, but there were also Bronze- and Iron Age finds as well as some Hellenistic material testifying to activities at this position. Late antique material has been thoroughly analyzed in terms of typology. Except for cooking ware produced in local workshops, other fragments can mostly be interpreted as import from workshops from two major late antique centers of production and distribution, North Africa and the eastern Mediterranean.